Risk assessment of debris flow disaster in mountainous area of northern Yunnan province based on FLO-2D under the influence of extreme rainfall - Ding, Xing-Yu; Hu, Wen-Jun; Liu, Fang; Yang, Xian (Frontiers in Environmental Science, 2023)
The stratum in Yunlong mountain area is unstable, and it is more likely to have extreme damage to the mountain in extreme rainfall weather, and even cause the occurrence of mountain disasters such as debris flow.This paper conducted field geological surveys and used the FLO-2D professional simulation system to scientifically evaluate the risk probability of three debris flow in Yunlong County.The risk prediction before and after engineering control was compared for the county's urban areas.in this paper, the construction drawings and remote sensing images of the treatment project are used to assist the positioning. After the simulation grid of debris flow is divided, the treatment project is added to the simulation project in the form of plug-in, and the specific engineering parameters are imported into the simulation project file by modifying its properties, so as to complete the setting of the treatment project in the numerical simulation and solve the problem of setting engineering measures.The probability analysis of debris flow under three different rainfall frequencies of 1%, 2% and 5%, namely once in 20 years, once in 50 years and once in 100 years, is simulated,and the flow and sedimentation characteristics of debris flow before and after engineering control are compared.The results show that under 5% rainfall frequency, the simulated results before engineering control were compared with the actual deposition range,and the evaluation accuracy is within a reasonable error range.After debris flow engineering control, the proportion of high risk areas of debris flow in urban areas decreased significantly, especially when the frequency of rainfall was once in 100 years, and the area of non-danger areas increased by 5.92% compared with that before control.In the end, this paper combines the depth of mud, the velocity of mud and the outbreak frequency to get the debris flow risk assessment map before and after engineering treatment, and puts forward suggestions for further prevention and control measures of debris flow disaster.The research results of this paper will provide good guidance for the occurrence and control of debris flow hazards under the influence of extreme rainfall in the mountainous area of northern Yunnan.